Peran Kepemimpinan Perempuan Dalam Perjanjian Lama - Grecetinovitria Merliana Butar- butar; Desy Mariana Siringoringo; Melias Sembiring (Jurnal Mahasiswa Kreatif, 2024)
The role and leadership of women in the cultural and religious context of ancient Israel, as recorded in the Old Testament of the Bible, is the focus of this research. Even though that period was dominated by a patriarchal societal structure, several women emerged as influential figures and main leaders. This research examines the contribution of female figures in shaping Israel's history and theology. Examples such as Deborah, Esther, Miriam, and Rahab highlight the important role of women in the history and development of Israelite religion, although they are often overlooked in theological and historical studies. This research confirms that women's leadership in the Old Testament not only reflects the position of women in ancient society, but also confirms that leadership is not exclusive to men. These stories illustrate that women in the Old Testament had the capacity and skills to lead effectively. They broke cultural norms and demonstrated that their leadership not only benefited the nation of Israel, but also honored God.